G20 COMMITMENT IN THE ACHIEVEMENT OF SDG 7: OPPORTUNITIES AND CHALLENGES - Muhamad Fathun, Laode; Darmastuti, Shanti (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2023)
Renewable energy is one of the issues that is the focus of every country, not only developed and developing countries. The energy transition is the focus of state policy in creating renewable energy. SDG 7 is one of the references for each country to oversee the energy transition policy towards renewable energy. One of the efforts made in helping each country to achieve the SDG 7 target is through international cooperation. One form of international cooperation that pays attention to renewable energy is the G20. Through the G20, it is hoped that there will be a collaboration between countries in efforts to achieve SDG 7 targets. Therefore, this article aims to analyze the opportunities and challenges faced by the G20 in implementing commitments to achieve SDGs7. Literature studies originating from official documents, journal articles, and internet sources are used to further analyze the opportunities and challenges facing the G20. The results of the study show that the G20 cooperation provides opportunities for member countries to be able to work together in achieving SDG 7, but the different characteristics and resources between developed and developing countries are a challenge in the energy transition process towards renewable energy.